Biochemical characterization and Biolog based identification of efficient Jute retting bacterial isolates from retting water - Ray, Syandan Sinha; Das, Suparna; Ali, Md. Nasim; Yeas, Lucina (Journal of Phytology, 2015)
Jute is considered as one of the cheapest natural fibre after cotton in terms of its production and uses. Retting is the most important post-harvest operation to yield high quality jute fibre and is solely carried out by various types of retting microorganisms. The present study was undertaken to screen and characterize the efficient retting microbes isolated from retting water based on their enzymatic activity followed by biolog based idenfication of those efficient microbes. These isolates were characterized on the basis of qualitative and quantitative estimation of Pectinolytic, Xylanase and Cellulase activity. Out of 40 isolated strains only 3 were finally identified as efficient jute retting microorganism having high pectinolytic and Xylanase activity coupled with less Cellulase activity. These identified three micro organisms may provide a suitable means to develop a new retting technique especially under water stress condition.